Impact of Soil test based Nutrient Management Technologies in Rice under KC Canal Command Area of Kurnool district of Andhra Pradesh - Ramanaiah, K.V.; Dhanalakshmi, G; Reddy, G Rajender; Murthy, A Krishna; Sudhakar, M (Journal of Agricultural Extension Management, 2019)
Frontline demonstrations were conducted from 2007 to 2011 in KC CanalCommand of Kurnool district, Andhra Pradesh to know the usefulness andeconomic advantage of soil test based nutrient management technology in rice.Five villages were identified and 10 farmers in each of the selected villageswere randomly chosen. At the beginning of the demonstrations a base linesurvey of selected farmers with respect to knowledge and adoption level ofdifferent nutrient management practices, rice production costs and productivitylevels was carried out. The demonstration of nutrient managementtechnologies covering seven nutrient management practices waS _conducted inthe selected farmers' fields under close supervision of Krishi Vigyan Kendrafor a period of five years. After five years, the impact of knowledge andadoption level of soil test based nutrient management technologies andproductivity enhancement in rice were assessed. The results clearly indicate animprovement in knowledge level, adoption level among the selected farmersbesides yield advantage and high net income over the existing practice ofnutrient application.